Structural basis for the antiarrhythmic blockade of a potassium channel with a small molecule. Issue 4 (5th January 2018) - Takemoto, Yoshio; Slough, Diana P.; Meinke, Gretchen; Katnik, Christopher; Graziano, Zachary A.; Chidipi, Bojjibabu; Reiser, Michelle; Alhadidy, Mohammed M.; Ramirez, Rafael; Salvador‐Montañés, Oscar; Ennis, Steven; Guerrero‐Serna, Guadalupe; et al.
Abstract : The acetylcholine‐activated inward rectifier potassium current ( I KACh ) is constitutively active in persistent atrial fibrillation (AF). We tested the hypothesis that the blocking of I KACh with the small molecule chloroquine terminates persistent AF. We used a sheep model of tachypacing‐induced, persistent AF, molecular modeling, electrophysiology, and structural biology approaches. The 50% inhibition/inhibitory concentration of I KACh block with chloroquine, measured by patch clamp, was 1 µM. In optical mapping of sheep hearts with persistent AF, 1 µM chloroquine restored sinus rhythm. Molecular modeling suggested that chloroquine blocked the passage of a hydrated potassium ion through the intracellular domain of Kir3.1 (a molecular correlate of I KACh ) by interacting with residues D260 and F255, in proximity to I228, Q227, and L299. 1 H 15 N heteronuclear single‐quantum correlation of purified Kir3.1 intracellular domain confirmed the modeling results. F255, I228, Q227, and L299 underwent significant chemical‐shift perturbations upon drug binding. We then crystallized and solved a 2.5 Å X‐ray structure of Kir3.1 with F255A mutation. Modeling of chloroquine binding to the mutant channel suggested that the drug's binding to the pore becomes off centered, reducing its ability to block a hydrated potassium ion. Patch clamp validated the structural and modeling data, where the F255A and D260A mutations significantly reduced I KACh block by chloroquine. With the use of numerical and structural biology approaches, we elucidated the details of how a small molecule could block an ion channel and exert antiarrhythmic effects. Chloroquine binds the I KACh channel at a site formed by specific amino acids in the ion‐permeation pathway, leading to decreased I KACh and the subsequent termination of AF.— Takemoto, Y., Slough, D. P., Meinke, G., Katnik, C., Graziano, Z. A., Chidipi, B., Reiser, M., Alhadidy, M. M., Ramirez, R., Salvador‐Montañés, O., Ennis, S., Guerrero‐Serna, G., Haburcak, M., Diehl, C., Cuevas, J., Jalife, J., Bohm, A., Lin, Y.‐S., Noujaim, S. F. Structural basis for the antiarrhythmic blockade of a potassium channel with a small molecule. FASEB J. 32, 1778–1793 (2018). www.fasebj.org